Gene therapy with mesenchymal stem cells expressing IFN‐ß ameliorates neuroinflammation in experimental models of multiple sclerosis. (12th January 2017) - Marin‐Bañasco, C; Benabdellah, K; Melero‐Jerez, C; Oliver, B; Pinto‐Medel, M J; Hurtado‐Guerrero, I; de Castro, F; Clemente, D; Fernández, O; Martin, F; Leyva, L; Suardíaz, M
Abstract : Background and Purpose: Recombinant IFN‐ß is one of the first‐line treatments in multiple sclerosis (MS), despite its lack of efficacy in some patients. In this context, mesenchymal stem cells (MSCs) represent a promising therapeutic alternative due to their immunomodulatory properties and multipotency. Moreover, by taking advantage of their pathotropism, these cells can be genetically modified to be used as carriers for delivering or secreting therapeutic drugs into injured tissues. Here, we report the therapeutic effect of systemic delivery of adipose‐derived MSCs (AdMSCs), transduced with the IFN‐β gene, into mice with experimental autoimmune encephalomyelitis (EAE). Experimental Approach: Relapsing–remitting and chronic progressive EAE were induced in mice. Cells were injected i.v. Disease severity, inflammation and tissue damage were assessed clinically, by flow cytometry of spleens and histopathological evaluation of the CNS respectively. Key Results: Genetic engineering did not modify the biological characteristics of these AdMSCs (morphology, growth rate, immunophenotype and multipotency). Furthermore, the transduction of IFN‐ß to AdMSCs maintained and, in some cases, enhanced the functional properties of AdMSCs by ameliorating the symptoms of MS in EAE models and by decreasing indications of peripheral and central neuro‐inflammation. Conclusion and Implications: Gene therapy was found to be more effective than cell therapy in ameliorating several clinical parameters in both EAE models, presumably due to the continuous expression of IFN‐β. Furthermore, it has significant advantages over AdMSC therapy, and also over systemic IFN‐ß treatment, by providing long‐term expression of the cytokine at therapeutic concentrations and reducing the frequency of injections, while minimizing dose‐limiting side effects.